الدقّة التشخيصية لسلّم ألفـرادو في التهاب الزّائدة الحادّ عند البالغين - علي, ماجد; قاسم, فؤاد حاج; حسن, أمجد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم الجراحة بمشفى الأسد الجامعي في اللاذقية، مدة الدراسة سنة واحدة (آب 2009 –آب 2010)، عدد المرضى 90 مريضاً متعاقباً حضروا إلى مركز الدراسة بشكاية ألم بطني حاد وقُيّموا بشكل استقبالي عن طريق سلّم ألفـرادو في قسم الإسعاف, وقبل العمل الجراحي حيث اعتمد التقييم السابق للجراحة بغض النظر عن فترة المراقبة ، أعطي المرضى علامات نوعية وقسّموا إلى مجموعتين حسب تنوع الأعراض: المجموعة الأولى: SCORE ≥ 7، المجموعة الثانية: . SCORE < 7 أجري العمل الجراحي لجميع المرضى بغضّ النظر عن الدرجة (مجرد وضع التشخيص)، ثمّ وُضِعَ التشخيص النهائي بعد الجراحة اعتماداً على التشريح المرضي، تمّ إثبات الفعالية اعتماداً على الحساسية والنوعية والقيمة التنبؤية. النتائج: تضمنت الدراسة 90 مريضاً: 52أنثى و 38ذكراً أثبت التشخيص في المجموعة الأولى عند 59\67، أثبت التشخيص في المجموعة الثانية عند 2\23. بلغت الحساسية: 96.72% ، والنوعية: 72.41%، والقيمة التنبؤية الإيجابية: 88.05 %، والقيمة التنبؤية السلبية: 91.3%. الخلاصة: يشكّل سلّم ألفـرادو وسيلة تشخيصية سهلة وبسيطة عند المرضى ذوي الأرقام الحديّة، كما ويمكن اعتماد السلّم كمعيار للقبول عند المرضى الذين يشتبه بوجود التهاب الزائدة الحادّ لديهم عند الأرقام الحديّة. Study is conducted in surgical ward, AL-ASSAD University Hospital in Lattakia. Duration of Study: it lasts for one year from August 2009 to August 2010. 90 consecutive patients who visited our surgical ward with acute appendicitis were assessed prospectively using Alvarado score in ER and before OR. We have depended on the latest assessment irrespective of the previous observation period. They were given specific scores according to the variable and divided into two groups: group one (score ≥7) group two (score <7). All patients were operated irrespective of score, if clinical diagnosis of acute appendicitis was made, postoperatively, diagnosis was confirmed by histopathology report. Validity of scoring system was assessed by calculating sensitivity, specificity and predictive value. Results: Total 90 patients were included in the study, which included 52 females and 38 males, at score ≥7: appendicitis was confirmed in 59\67, while at score <7 appendicitis was confirmed in 2\23, the sensitivity was 96.72 %, specificity was 72.41%, positive predictive value was 88.05%, and negative predictive value 91.3%. Conclusion: The Alvarado score is a simple, easy scoring at both end of scale. It can be used as an admission criterion in patients with suspected appendicitis at both end of scale.